2008
DOI: 10.3147/jsfp.43.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Temperature on Mortality and Virus Shedding in Carp Experimentally Infected with Koi Herpesvirus

Abstract: ABSTRACT-Common carp Cyprinus carpio were experimentally exposed to koi herpesvirus (KHV) under water temperature regimes ranging from 16∞C to 28∞C. Fish maintained at 16∞C, 23∞C and 28∞C died due to infection at 21 -52, 5 -20 and 7 -14 days post-virus exposure (dpe), respectively. Cohabitation experiments in which KHVinfected common carp were kept with naive koi carp revealed that infectious virus was continuously shed from the infected common carp for 34 days (7-40 dpe) at 16∞C, for 14 days (1-14 dpe) at 23∞… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 8 publications
3
39
1
Order By: Relevance
“…High seawater temperatures appear to be one of the potential factors likely to induce OsHV-1 infection. This hypothesis is consistent with observations on koi herpesvirus, for which temperatures between 18°C and 28°C favored the onset and severity of disease in fish (35)(36)(37)(38)(39)(40). Field surveys conducted in Japan showed that the lowest water temperature at which outbreaks occurred was 15.5°C to 16°C (36,39).…”
Section: Discussionsupporting
confidence: 90%
“…High seawater temperatures appear to be one of the potential factors likely to induce OsHV-1 infection. This hypothesis is consistent with observations on koi herpesvirus, for which temperatures between 18°C and 28°C favored the onset and severity of disease in fish (35)(36)(37)(38)(39)(40). Field surveys conducted in Japan showed that the lowest water temperature at which outbreaks occurred was 15.5°C to 16°C (36,39).…”
Section: Discussionsupporting
confidence: 90%
“…Experimentally, KHVD has been reproduced in temperatures ranging from 16 to 28°C (Gilad et al, 2003(Gilad et al, , 2004Yuasa, Ito, & Sano, 2008) and the lowest temperature associated with a CyHV-3 outbreak was 15.5°C in a field survey in Japan (Hara, Aikawa, Usui, & Nakanishi, 2006). Interestingly, CyHV-2 induces mortalities in goldfish at a slightly enlarged temperature range from 15 to 30°C (Ito & Maeno, 2014) suggesting a similar but adaptable temperature range in cyprinid herpesviruses.…”
Section: Effect Of Water Temperaturementioning
confidence: 88%
“…Interestingly, CyHV-2 induces mortalities in goldfish at a slightly enlarged temperature range from 15 to 30°C (Ito & Maeno, 2014) suggesting a similar but adaptable temperature range in cyprinid herpesviruses. In CyHV-3 infections, the onset of mortality was affected by the water temperature; the first mortalities occurred between 5-8 and 14-21 dpi when the fish were kept between 23-28 and 16-18°C, respectively (Gilad et al, 2003;Yuasa et al, 2008). Moreover, daily temperature fluctuations of AE3°C induce important stress in fish, which increases cortisol release in the water and also their susceptibility to CyHV-3 (higher mortality rate and viral excretion) (Takahara et al, 2014).…”
Section: Effect Of Water Temperaturementioning
confidence: 99%
“…The infected fish begin to die within 1 or 2 days after the onset of the symptoms [34]. During infection, virulent virus is shed continuously via feces, urine, gills and skin mucus for a longer period from infected common carp at 16°C than those at 23-28°C [90]. Massive mortalities occur within a week of onset of clinical signs, with the mortality rate reaching 80-100 % [84].…”
Section: Transmissionmentioning
confidence: 99%